2020
DOI: 10.1021/acssuschemeng.0c08167
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-Flow Production of Isosorbide from Aqueous-Cellulosic Derivable Feed over Sustainable Heterogeneous Catalysts

Abstract: Continuous-flow sorbitol dehydration in liquid water was performed on β zeolite (Si/Al molar ratio = 75) with conversion of 94 and 83 mol % isosorbide yield. This efficiency is due to the three-dimension pore architecture, high specific surface area (520 m2 g–1), and Brønsted acid sites of 69 μmol g–1. The pore size of β zeolite (6.6 × 6.7 Å2) is slightly larger than the cross section of sorbitol and isosorbide and enables an efficient diffusion of the reactant and product to/from the pores. Operation in conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 78 publications
2
34
0
Order By: Relevance
“…Then on-detected Al in pyridine-IR measurements should mainly correspond to those Al contents in sod cage or to weak acid Al species. [46][47][48] These results explicitly confirm that unique Al distributions have been obtained in the high-silica FAUz eolites prepared via the presented cooperative OSDAs trategy,w hich has never been reported before in literature regarding high-silica FAUz eolites.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Then on-detected Al in pyridine-IR measurements should mainly correspond to those Al contents in sod cage or to weak acid Al species. [46][47][48] These results explicitly confirm that unique Al distributions have been obtained in the high-silica FAUz eolites prepared via the presented cooperative OSDAs trategy,w hich has never been reported before in literature regarding high-silica FAUz eolites.…”
Section: Resultssupporting
confidence: 85%
“…[30,33] FAU-S1 and FAU-S2 were selected because of their pure FAUphase obtained with high seeds loading (10 %) at different temperatures (110 8 8Ca nd 120 8 8C, respectively);h ighly siliceous FAU-S3 and FAU-S4 were chosen because of their minute seed usage (1 %), which would not significantly change the overall gel composition, but translates to ahigher seeding efficiencyand apotentially lower manufacturing cost as indicated by the solid product yields (Table S2, entries 26-29, entries 39-42). In consideration of the gel composition differences between the highsilica FAUa nd the two benchmark samples (e.g.N a + ,H 2 O, seeds amount), another six benchmark recipes were carried out with similar synthesis compositions of FAU-S4 but using CE or Ch + as the only OSDA( so digressing from reported "CE or Ch + only" recipes in literature) (Table S2, entries [46][47][48][49][50][51]. Themajority product in all these benchmark recipes was never FAU( Figures S8,S9).…”
Section: Resultsmentioning
confidence: 99%
“…68 The XRD diffraction patterns of the spent catalyst after 9 h of TOS (35Ni/NDC-TOS) showed similar peaks to the spent catalyst after 1 h (Figure S22 One of the advantages of operating in continuous flow systems is the possibility to couple multiple reactors together. 67 Herein, two identical packed reactors with 35Ni/NDC have been coupled in series, in order to prolong the contact time between the LS solution and the catalyst and consequently optimize the monomer yield (Figure 6 and Figure S5 in ESI). Moreover, coupling two flow reactors in series aims to mimic an industrial scale up of such process.…”
Section: Process Optimizationmentioning
confidence: 99%
“…64,65 All these studies were performed in batch systems, which presents disadvantages when compared to continuous flow systems, e.g., complex product-catalyst separation, time, energy-consumption in discontinuous steps and cost efficiency . 10,12,59,66,67 Horáček et al 52 only reported the LS fragmentation in a continuous flow system at a high reaction temperature (320°C) over bimetallic Ni and Mo catalyst supported on Al 2 O 3 . In this study and due to over hydrogenation, guaiacol was found the major product of LS catalytic fragmentation (yield higher than 1.8 wt.-%).…”
Section: Introductionmentioning
confidence: 99%
“…33 At present, isosorbide production has attracted widespread attention and is anticipated to reach US $324.6 million in the next few years. 34,35 Several facile synthetic strategies for DMI have been reported 33,36,37 to increase its availability at a cheaper price. The close proximity of the Hildebrand solubility parameters (d T ) of DMI to PVDF suggests its suitability as a dissolution solvent.…”
Section: Introductionmentioning
confidence: 99%